The Short and Longer Term Potential Welfare Impact of Global Commodity Inflation in Tanzania - Dessus, Sébastien (World Bank, Washington, DC, 2012)
This paper uses a computable general equilibrium model to assess the welfare impact of commodity price inflation in Tanzania and possible tax policy responses in the short, medium, and long term. The results suggest that global commodity inflation since 2006 may have had a significantly negative impact on all Tanzanian households. Most of the negative impact comes from the rise in the price of oil. In contrast, food price spikes are potentially welfare improving for all Tanzanian households in the medium to long run. In comparison with nonpoor households, poor households in Tanzania may be relatively shielded from global commodity inflation because they derive a larger share of their incomes from agricultural activity and consume less oil-intensive products. Finally, the results suggest that tax policies encouraging greater agricultural production and consumption may help to reduce poverty. In contrast, policies discouraging agricultural production (such as export bans) bear the risk of increasing poverty in the long run. However, such policies would only effect at the margin (in one direction or the other) the likely impact of global commodity inflation on poverty.